Bimbingan Teknis Budidaya Magot untuk Optimalisasi Pengelolaan Sampah Organik di Pesantren Wahdah Islamiyah: Technical Guidance on Magot Cultivation for Optimizing Organic Waste Management in Wahdah Islamiyah Pesantren - Ariesman M.; Hariadi, Hariadi; La Jumadin (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2025)
Islamic boarding schools as educational institutions produce large amounts of organic waste that can cause environmental problems if not managed properly. However, through this Community Service Program (PKM), organic waste can be processed into useful resources through maggot cultivation (Black Soldier Fly). Using the Asset-Based Community Development (ABCD) method, this PKM aims to increase students' and Islamic boarding school managers' awareness of the potential of organic waste and provide education and technical guidance on organic waste management. The results of the activity showed that participants had increased awareness and understanding that the abundant organic waste in Islamic boarding schools can be managed effectively through maggot cultivation. In addition, participants also gained technical knowledge about maggot cultivation, both in theory and practice, which was reinforced by direct visits to maggot cultivation locations. Participants were also given practical materials to be applied in their respective places. The main contribution of this PKM is the creation of a more ecological and productive mindset in managing organic waste in Islamic boarding schools while opening up economic opportunities through the use of maggots as animal, fish, and bird feed.